2018
DOI: 10.2131/jts.43.407
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the applicability domain for highly volatile substances on the Short Time Exposure test method and the predictive performance in assessing eye irritation potential

Abstract: The Short Time Exposure (STE) test method is an in vitro method for assessing the eye irritation potential of chemicals and is used to classify the Globally Harmonized System of Classification and Labelling of Chemicals (GHS) Category 1 and No Category (NC). The method has been adopted by the Organisation for Economic Co-operation and Development (OECD) as test guideline (TG) 491 since 2015. While this method can be used to classify GHS NC, it is not suitable for testing highly volatile substances and solids o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…As a result, we obtained cell viabilities of 31% at 5% dilution and 18.7% at 0.05% dilution. These cell viabilities did not show dose dependence, which was also not reported except for this substance in previous STE test data (Abo et al, 2018). When we performed an additional confirmation experiment using GC-FID, this substance was detected at 0.524 mg in wells exposed to 5% dilution but was not detected in wells exposed to 0.5% dilution (Table 6).…”
Section: Discussionsupporting
confidence: 79%
“…As a result, we obtained cell viabilities of 31% at 5% dilution and 18.7% at 0.05% dilution. These cell viabilities did not show dose dependence, which was also not reported except for this substance in previous STE test data (Abo et al, 2018). When we performed an additional confirmation experiment using GC-FID, this substance was detected at 0.524 mg in wells exposed to 5% dilution but was not detected in wells exposed to 0.5% dilution (Table 6).…”
Section: Discussionsupporting
confidence: 79%
“…It is recommended that SIRC cells are obtained from a well-qualified cell bank, such as American Type Culture Collection CCL60. ©OECD 2020 15.…”
Section: Preparation Of the Cellular Monolayermentioning
confidence: 99%
“…measured vapour pressure > 6kPa) and solid substances other than surfactants are excluded from the dataset, the overall accuracy ©OECD 2020 improves to 90% (92/102), the false negative rate to 2% (1/54), and the false positive to 19% (9/48) (7). Further work demonstrated that highly volatile substances can be correctly tested when using mineral oil instead of saline as a solvent (15). The accuracy of the STE test for highly volatile substances (i.e.…”
mentioning
confidence: 99%
“…[ 4 ] There are several in-vivo and in-vitro studies on the toxicity of these products. [ 5 ] Of particular interest is the Draize rabbit eye and skin irritancy tests, which evaluated the in-vivo irritation potential of these products on the skin and eye. Another important finding was that the eye is more sensitive to the toxic/allergic effects of ABHRs than the skin.…”
mentioning
confidence: 99%